The Low umbilical cord Zinc levels Lead to Atopic Allergic Infants : a Cohort study during 0-4 months of Age - Priyantini, Sri; Suprihati, -; Widyastiti, Nyoman Suci; Soemantri, - (Bangladesh Journal of Medical Science, 2019)
Background: The research on association between differentiation of Th1 and Th2 were previously conducted on experimental animals. The study on association between umbilical cord zinc and the risk of allergy symptoms during early stage of life has not been conducted in Indonesia. Studies on zinc and allergies are commonly investigated during adulthood and the results are still contradictive. Objective: The aim of the study is to determine the extent of zinc’s role in the emergence of atopic allergy symptoms during the first 4 months age Methods: This prospective cohort study includes consecutive 80 healthy newborns followed up for 4 months after birth at Semarang Sultan Agung Islamic Hospital and Bangetayu Primary Health Care. Hypothesis testing were analyzed with unpaired t-test , chi-square test or fisher’s test Results: The mean value of cord blood zinc in allergic infants were significantly lower when compared with non atopic allergy (74.1 ± 17.3 μg / dL vs 91.5 ± 22.6 μg / dL, p=0.029). Very early formula feeding were 4.4 times more at risk of suffering from allergies(p=0.023). Conclusion: Umbilical cord zinc levels are associated with atopic allergy symptoms for the first 4 months of life. Formula feeding before 1 month of age was associated with atopic allergic infants Bangladesh Journal of Medical Science Vol.19(1) 2020 p.114-121